PEMIKIRAN NASR HâMID ABû ZAYD TENTANG FIQH AL-TA’WîL WA AL-TAFSîR - Kholid, Abd (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
Abû Zayd was born on july 1, 1943 in a village called Tanta, the provincial capital of al-Gharbîyah, Egypt. Abû Zayd is very concerned with the study of the Koran. Several important works were written al-Ittijâh al-?Aqlî fî al-Tafsîr: Qadîyat al-Majâz ?ind al-Mu?tazilah al-Wasatîyah and Naqd al-Khitâb al-Dînî. intellectual adventure Abû Zayd peaked when he wrote a short treatise as one of the main requirement professor appointment at the university of Cairo. Abû Zayd has given the feel of a more powerful, though that?s not easily penetrate the fortress-establishment of religious understanding which is wrapped in the name of